Fresno County Bar Association's Barristers Benefit Ball at the Fresno Metropolitan Museum - Watkins, Howard::::::::: (1988)
Cheryl Berman, Richard Berman, Jim Donabed, Linda Donabed, Richard Cenci, and Kelly Alcozer